South Sudan : the untold story : from independence to civil war - Johnson, Hilde F.; Tutu, Desmond (2018)
"In July 2011, South Sudan was granted independence and became the world's newest country. Yet just two-and-a-half years after this momentous decision, the country was in the grips of renewed civil war and political strife. Hilde F. Johnson served as Special Representative of the Secretary-General and Head of the United Nations Mission in the Republic of South Sudan from July 2011 until July 2014 and, as such, she was witness to the many challenges which the country faced as it struggled to adjust to its new autonomous state. In this book, she provides an unparalleled insider's account of South Sudan's descent from the ecstatic celebrations of July 2011 to the outbreak of the disastrous conflict in December 2013 and the early, bloody phase of the fighting. Johnson's frequent personal and private contacts at the highest levels of government, accompanied by her deep knowledge of the country and its history, make this a unique eyewitness account of the turbulent first three years of the world's newest - and yet most fragile - country."--Publisher's description.
A dream comes true -- A country without a state -- An incomplete divorce -- Jonglei: the UN -- between a rock and a hard place -- The leadership -- The nightmare -- The heart of the matter: security -- Waging peace in South Sudan.
Includes bibliographical references (pages 362-367) and index.
Keywords: Johnson, Hilde F; Since 2000; Civil war -- South Sudan; Civil war; Politics and government; South Sudan -- History -- 21st century; South Sudan -- Politics and government -- 2011-; South Sudan; History